Adaptation Technique in the Translation of Literary Texts (as Exemplified in the Translation of French and English Literary Texts) - Polina Sergeevna Tasenko; Natalia Yur'evna Nelyubova; Viktor Ivanovich Ershov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2016)
This article describes some particularities of translation of literary texts from French and English into Russian as exemplified in the novel “The Lady of the Camellias” by A. Dumas and the novel “Wuthering Heights” by E. Brontë. The article examines in particular the use of the adaptation technique in order to confirm the hypothesis of the connection of this translation transformation with conveyance of the original's stylistic features. This transformation is applied in the translation of some phenomena and phrases in the original text that can barely be translated because of their national singularity, a significant time gap, or peculiarity for other culture bearers. The theoretical foundation for the article are literary style researches [Barkhudarov, 1975; Komissarov, 1990; Chaikovskij, 1997; Chukovskij, 2014; Baker, 2011], as well as researches in the field of the use of adaptation in the translation of literary texts [Alekseeva, 2004; Vlakhov, Florin, 1980; Shchetinkin, 1987; Clifford, Landers, 2001; Newmark, 1988]. The research methods used in the study are the following: relevant scientific literature analysis, statistical approach, comparative study of literary texts and their translations. A thorough analysis of the nature of adaptation enabled us to specify a range of translation transformations which allow adaptation to be applied in the reanslation of literary texts. According to the results of the research, the informative as well as the aesthetic function plays a very important role in the translation of literary texts.